2018
DOI: 10.1001/jamasurg.2018.1166
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Year Analysis of Nonbattle Injury Among US Service Members Deployed to Iraq and Afghanistan

Abstract: In this study, approximately one-third of injuries during the Iraq and Afghanistan wars resulted from NBI, and the proportion of NBIs was steady for 12 years. Understanding the possible causes of NBI during military operations may be useful to target protective measures and safety interventions, thereby conserving fighting strength on the battlefield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…The mechanisms of injury identified in this review are similar to those reported in military populations [46,47,48]. For example, in the Australian Defence Force, slips, trips and falls were identified as the leading mechanism of injury (21.4%) [46].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The mechanisms of injury identified in this review are similar to those reported in military populations [46,47,48]. For example, in the Australian Defence Force, slips, trips and falls were identified as the leading mechanism of injury (21.4%) [46].…”
Section: Discussionsupporting
confidence: 58%
“…Considering this, body stressing, which was the fourth most common mechanism of injury (16.3%), was the mechanism associated with the highest number of working days lost (26.9%), followed by slips, trips and falls (25.2%). Even in an operational military combat theatre, falls have been identified as the leading site of nonbattle injuries, accounting for 21.3% of injuries sustained by US service members deployed to Iraq and Afghanistan over a 12-year period [48]. As such, strategies to prevent slips, trips and falls, as well as muscle stressing, may impact both firefighter and military populations.…”
Section: Discussionmentioning
confidence: 99%
“…The recorded prevalence of battle-injured parents (0.3%) in this study was low compared with recent statistics of war-related injuries in ADSMs. 51 Discrepancies likely relate to miscoding of injuries if diagnoses were made after the acute injury period, such as PTSD and TBI, which may take time to develop, or challenges related to completing accurate documentation in combat settings.…”
Section: Discussionmentioning
confidence: 99%
“…Female soldiers have been found to suffer injuries at a higher rate, both in training (9,10) and on operations (11,12) when compared to their male colleagues, although this sex-based difference does not hold true across all military contexts and in some contexts male personnel have been observed to have higher injury rates than female personnel (13,14). There is also evidence that female soldiers may sustain injuries to different body sites when compared to male soldiers (15)(16)(17) and exhibit some differences in risk factors for injury, due to anthropometric, biomechanical, and anatomical differences.…”
Section: Introductionmentioning
confidence: 99%